Molecular Characterization of Carbapenem-Resistant Enterobacteriaceae in the USA, 2011–2015. (4th October 2017) - Ansari, Uzma; Lawsin, Adrian; Campbell, Davina; Albrecht, Valerie; McAllister, Gillian; Bulens, Sandra; Walters, Maroya Spalding; Jacob, Jesse T; Satola, Sarah W; Wilson, Lucy E; Lynfield, Ruth; Vagnone, Paula M Snippes; et al.
Abstract: Background: Carbapenem-resistant Enterobacteriaceae (CRE) have emerged as an important cause of healthcare-associated infections. We characterized the molecular epidemiology of CRE in isolates collected through the Emerging Infections Program (EIP) at the Centers for Disease Control and Prevention (CDC). Methods: From 2011–2015, 8 U.S. EIP sites (CO, GA, MD, MN, NY, NM, TN and OR) collected CRE ( Escherichia coli, Enterobacter aerogenes, Enterobacter cloacae complex, Klebsiella pneumoniae, and Klebsiella oxytoca) isolated from a normally sterile site or urine. Isolates were sent to CDC for reference antimicrobial susceptibility testing and real-time PCR detection of carbapenemase genes ( bla KPC, bla NDM, bla OXA-48 ). Phenotypically confirmed CRE were analyzed by whole genome sequencing (WGS) using an Illumina MiSeq benchtop sequencer. Results: Among 639 Enterobacteriaceae evaluated, 414 (65%) were phenotypically confirmed as CRE using CDC's current surveillance definition (resistant to ertapenem, imipenem, doripenem, or meropenem). Among isolates confirmed as CRE, 303 (73%) were carbapenemase-producers (CP-CRE). The majority of CP-CRE originated from GA (39%), MD (35%) and MN (11%); most non-CP-CREs originated from MN (27%), CO (25%) and OR (17%). K. pneumoniae was the predominant carbapenemase-producing species (78%) followed by E. cloacae complex spp (12%), E. coli (7.9%), E . A erogenes (0.9%) and K. oxytoca (0.6%). The most common carbapenemase genes detected were bla KPC-3 (76%) and bla KPC-2 (19%); bla NDM and bla OXA-48 -like genes were detected in 1.6% and 0.3% of isolates, respectively. For carbapenemase-producing K. pneumoniae, Enterobacter spp, and E. coli, the predominant sequence types (ST) were ST258 (65%), ST171 (35%) and ST131 (29%), respectively. Conclusion: The distribution of CP and non-CP-CRE varied across the catchment sites. Among CP-CRE, KPC-producing K. pneumoniae predominated; other carbapenemases were rarely identified in the locations under surveillance. Strain types known to have increased epidemic potential (ST258 and ST131) were common among carbapenemase-producing K. pneumoniae and E. coli isolates, respectively. Disclosures: All authors: No reported disclosures.